Independent evaluation of IFC's development results 2007 : lessons and implications from 10 years of experience (International Finance Corporation WashingtonUS, 2007)
Looks back at the development results that IFC-supported projects have achieved in the last 10 years, the main lessons that have emerged at the project level, and the strategic implications for IFC going forward, in the context of rapid organizational growth.
Keywords: IFC